Zakon vlahom (Ius Valachicum) in the charters issued to Serbian medieval monasteries and kanuns regarding Vlachs in the early ottoman tax registers (defters) - Luković, Miloš (Balcanica Posnaniensia. Acta et studia, 2015)
The transhumant type of livestock breeding (mostly sheep, sometimes goats) in the Balkans has Old Balkan roots. It was most frequent in the Balkans in the Middle Ages. This type of livestock breeding was pursued by the locals – Vlachs (even before the arrival of the Slavs), as their only professional activity. Over time, it became very popular, being also adopted by the population of Slavic origin. In the Serbian medieval state, as well as in other Balkan Christian states, there were no regulations that would uniformly regulate the position of the Vlachs. Regulations regarding the position of the Vlachs can usually be found in the foundation or donation charters of the monasteries. In the few charters from the first half of 14th century rules regarding the Vlachs were grouped under the common name <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Zakon Vlahom. Apart from this, common law applied to them as well. In conquering the Christian lands in the Balkans in the 14th and 15th centuries, the Ottoman state initially held certain lands and regions in a vassal status, and the sanjaks were formed following their definite subjugation and the liquidation of the vassal status, within the subjugated lands or regions. After the formation of a particular sanјak a tax list was immediately established, and that is how Ottoman Tax Registers (<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">defters) were created. In each defter of the particular sanјak in the early Ottoman period (second half of the 15th and the beginning of the 16th century) there existed a regulation known as <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">kanun, regulating the duties of the Vlachs. They contained rules and legal traditions of common law, that had existed earlier in the territories of the subjugated Balkan Christian states.